Peran Suami Mualaf Terhadap Pembentukan Keluarga Sakinah - Nur Fatkurohman; Fitrohtul Khasanah; Najih Abqori (Institut Agama Islam (IAI) Faqih Asy'ari Kediri, 2025)
This study examines the role of convert husbands in forming a peaceful family in Islam. The background of this study is related to the increasing number of individuals who embrace Islam, often because of the need to fulfill marriage requirements. The main objective of this study is to analyze how converted husbands adapt to Islamic values ​​in building a peaceful family, with a focus on the role of husbands as leaders, protectors, and educators in creating a harmonious family environment. This study was conducted through the Mualaf Center institution in Yogyakarta with a qualitative approach through interviews with three couples of convert families. The findings of the study indicate that despite facing challenges in adjusting to a new religious identity, the role of convert husbands in forming a family full of peace, love, and spirituality is very important. Husbands play an important role in educating children, maintaining household harmony, and strengthening the spiritual foundation of the family. This study provides valuable insights into the dynamics of convert families in Muslim society and the important role of convert husbands in forming a peaceful family.